The Value of Aggregated City Scale Models to Rapidly Assess SuDS in Combined Sewer Systems - Muhandes, Samer; Dobson, Barnaby; Mijic, Ana (Frontiers in Water, 2022)
The role of Sustainable Drainage Systems (SuDS) in reducing combined sewer overflows (CSOs) and flood volumes can be accurately assessed using the available high-fidelity sewer network modelling software packages in the market. However, these tools are too slow for a range of modern applications such as optimisation or uncertainty analysis where long-term climate projection simulations are required. In this study, we create a novel representation of combined sewer systems to enhance an existing spatially aggregated model (CityWat) with additional functionalities to assess flood volumes, discharge to rivers and CSOs. We validate the developed model (CityWatStorm) by comparing the simulation results with a high-fidelity InfoWorks ICM model. Finally, we implement SuDS at a city scale and assess the betterment achieved in the context of flood volumes and CSOs. We conclude that CityWatStorm is able to capture the SuDS betterment with 95% accuracy, and the total flood volume and CSOs within an accuracy ranging from 78% to 83%. This makes the aggregated model suitable for a wide range of applications such as sensitivity analysis of catchment interventions for long-term planning under future uncertainties.